Thermoregulation by an Australian murine rodent, the ash-grey mouse (Pseudomys albocinereus) - Barker, Justine; Cooper, Christine; Withers, Philip; Cruz-Neto, A. (Elsevier Inc., 2012)
We examine here the thermal physiology of the ash-grey mouse, as there is a paucity of data to explain how Australian rodents meet thermoregulatory demands. Most ash-grey mice remained normothermic over a range of ambient temperatures (10 °C to 30 °C), although they became hyperthermic at high ambient temperatures. One individual entered torpor at ambient temperatures of 20 °C and 25 °C, with minimal body temperatures of 24.5 °C and 28.4 °C respectively, before spontaneously arousing. This is the first evidence of torpor use by an Australian murine rodent. Our data suggest that although ash-grey mice have the physiological ability to use torpor, it is used rarely, presumably due to other behavioural and physiological adaptations. Their higher-than-expected basal metabolic rate (1.56 ± 0.25 mL O2 g− 1 h− 1) indicates that ash-grey mice do not have a frugal approach to energy expenditure. Other standard physiological variables were typical of a generalised rodent. A readily-available omnivorous diet, nocturnal activity, semi-fossorial habit and social behaviour presumably allow a high energy lifestyle. A reluctance to use torpor, despite an apparent physiological ability to do so, supports the idea that the use of torpor reflects a net balance between the costs and benefits of a heterothermic thermoregulatory strategy.